A Symphony of Movement. Road Traffic Rules and Traffic Accidents in the First Republic of Lithuania - Adomas Žirlys (Lietuvos Istorijos Studijos, 2022)
The article examines the laws and rules governing traffic on streets and roads published in the First Republic of Lithuania, as well as statistical data on traffic accidents. Centralised legal regulation of traffic did not begin until the late 1930s, but within a short period of time three successive laws were published. In the mid-1930s, such a law regulated not only the movement of motor vehicles, but also all non-motorised vehicles and pedestrians. At the same time, statistics on road accidents began to be collected. It is clear from these statistics that, despite strict traffic regulation and sluggish motorisation, the number of accidents has steadily increased.